Orthopaedic knowledge update musculoskeletal infection - Cierny, George 525797; McLaren, Alex C. 525798; Wongworawat, Montri D., 1973- 525799; American Academy of Orthopaedic Surgeons 2186; Musculoskeletal Infection Society 525800 (New York : Amer Academy of Orthopaedic Surgeons, 2009)
Includes bibliographical references and index